2022
DOI: 10.1186/s12904-022-01105-0
|View full text |Cite
|
Sign up to set email alerts
|

Presuppositions, cost–benefit, collaboration, and competency impacts palliative care referral in paediatric oncology: a qualitative study

Abstract: Background Although a significant proportion of children with cancer need palliative care, few are referred or referred late, with oncologists and haematologists gatekeeping the referral process. We aimed to explore the facilitators and barriers to palliative care referral. Methods Twenty-two paediatric oncologists and haematologists were purposively recruited and interviewed. Data were analysed using reflexive thematic analysis. Findings were inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(46 citation statements)
references
References 97 publications
3
43
0
Order By: Relevance
“…The perception of self-e cacy in uences cognitive and affective processes and impacts social behaviour and action (77). In the study (55), only a small number of oncologists perceived self-e cacy in providing palliative care. Most oncologists valued the bene t of palliative care referral and acknowledged their constraints regarding the limits to their skills and knowledge needed to provide palliative care.…”
Section: A Human Cognition and Emotionsmentioning
confidence: 95%
See 4 more Smart Citations
“…The perception of self-e cacy in uences cognitive and affective processes and impacts social behaviour and action (77). In the study (55), only a small number of oncologists perceived self-e cacy in providing palliative care. Most oncologists valued the bene t of palliative care referral and acknowledged their constraints regarding the limits to their skills and knowledge needed to provide palliative care.…”
Section: A Human Cognition and Emotionsmentioning
confidence: 95%
“…In the review (54), oncologists expressed self-e cacy in catering to palliative care needs. However, the study (55) found that oncologists had mixed feelings about their ability to respond appropriately to these needs. Perceived self-e cacy is a person's belief about their capabilities to produce a level of performance to accomplish a task that meets the expectation of the self and others (77).…”
Section: A Human Cognition and Emotionsmentioning
confidence: 95%
See 3 more Smart Citations